Altered expression and activity of phase I and II biotransformation enzymes in human liver cells by perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS). (30th January 2020) - Franco, Marco E.; Sutherland, Grace E.; Fernandez-Luna, Maria T.; Lavado, Ramon
Abstract: Human exposure assessments for perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) have been mostly limited to the quantification of these chemicals in different environmental matrices, but only a few studies have addressed toxicological aspects associated with them. It has been suggested that both PFOA and PFOS are highly stable chemicals that are not metabolized, yet previous reports have described abnormal activity of important biotransformation pathways. Therefore, the goal of the present study was to investigate the effects of PFOA and PFOS on phase I and II biotransformation enzymes at the gene expression and activity levels, and by using the well-established human liver HepaRG cell line. Cells were exposed to a wide range of PFOA and PFOS concentrations for 24 or 48 h, prior to cytotoxicity measurements, and quantification of expression and activity of three cytochrome P450 enzymes (CYP1A2, CYP2C19 and CYP3A4) and two conjugation enzymes (glutathione-S-transferase (GST-M1) and UDP-glucuronosyltransferase (UGT-1A1)). Expression of all CYP enzymes was significantly reduced from exposure to both PFOA and PFOS after 48 h and from concentrations as low as 40−50 ng/L, with CYP3A4 also presenting the lowest activity. Among the conjugation enzymes, the expression of UGT was significantly reduced only by PFOA after 48 h of exposure, yet no significant alterations in its activity were observed. While the specific chemico-biological interactions of these compounds with gene expression and biotransformation pathways is not clear, the results from this study suggest that the interference of PFOA and PFOS with phase I and II biotransformation enzymes could potentially lead to adverse outcomes resulting from the inability of biotransformation pathways to function as needed.